Pengaruh Penerimaan Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Musi Rawas Utara - Subianto Subianto; Miki Indika; Hengki Febriansa (Jurnal Kajian Akuntansi dan Auditing, 2019)
The purpose of this study is to investigate the influence of local tax revenue and retribution toward local revenue of North Musi Rawas. The sample is North Musi Rawas Region. To collect the data, this study uses secondary data method. The regression analysis is used to test the hypothesis. The results showed that the The regional tax and Regional retribution did didn’thave a significant effect on Local Revenue (PAD. It means all the hypothesis proposed in this study were rejected.